Molecular mechanism of palmitic acid and its derivatives in tumor progression - Wang, Xitan; Zhang, Chaonan; Bao, Na (Frontiers in Oncology, 2023)
Palmitic acid (PA) is a saturated fatty acid commonly found in coconut oil and palm oil. It serves as an energy source for the body and plays a role in the structure and function of cell membranes. Beyond its industrial applications, PA has gained attention for its potential therapeutic properties. Modern pharmacological studies have demonstrated that PA exhibits anti-inflammatory, antioxidant, and immune-enhancing effects. In recent years, PA has emerged as a promising anti-tumor agent with demonstrated efficacy against various malignancies including gastric cancer, liver cancer, cervical cancer, breast cancer, and colorectal cancer. Its anti-tumor effects encompass inducing apoptosis in tumor cells, inhibiting tumor cell proliferation, suppressing metastasis and invasion, enhancing sensitivity to chemotherapy, and improving immune function. The main anticancer mechanism of palmitic acid (PA) involves the induction of cell apoptosis through the mitochondrial pathway, facilitated by the promotion of intracellular reactive oxygen species (ROS) generation. PA also exhibits interference with the cancer cell cycle, leading to cell cycle arrest predominantly in the G1 phase. Moreover, PA induces programmed cell autophagy death, inhibits cell migration, invasion, and angiogenesis, and synergistically enhances the efficacy of chemotherapy drugs while reducing adverse reactions. PA acts on various intracellular and extracellular targets, modulating tumor cell signaling pathways, including the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt), endoplasmic reticulum (ER), B Cell Lymphoma-2 (Bcl-2), P53, and other signaling pathways. Furthermore, derivatives of PA play a significant regulatory role in tumor resistance processes. This paper provides a comprehensive review of recent studies investigating the anti-tumor effects of PA. It summarizes the underlying mechanisms through which PA exerts its anti-tumor effects, aiming to inspire new perspectives for the treatment of malignant tumors in clinical settings and the development of novel anti-cancer drugs.